The Effect of Tax Knowledge Level on Land and Building Taxpayer Compliance in Cimanggung District - Dian Rifky Maulana; Nining Kurniasih; Sophia Annisa R (LPPM Universitas Sebelas April, 2021)
This study aims to examine and obtain evidence regarding the level of tax knowledge that affects the compliance of land and building taxpayers in Cimanggung District. Tax knowledge is tax information that can be used by taxpayers as a basis for making decisions, and to take certain directions or strategies in relation to the implementation of rights and obligations in the field of taxation. Meanwhile, compliance is the backbone of the self-assessment system, in which the taxpayer is responsible for determining his/her own tax obligations and then paying and reporting the tax in an accurate and timely manner. The method used in this research is descriptive quantitative method. The data collection technique was obtained from the results of interviews, questionnaires, observations, and library research. Further testing of validity, reliability, classical assumption test, simple regression analysis, coefficient of determination test and hypothesis testing. Based on the results of research on the effect of tax knowledge on land and building taxpayer compliance in Cimanggung District, it can be concluded that, tax knowledge (X) has a positive and significant effect on land and building taxpayer compliance (Y). The results of statistical calculations show that the t count is 8.835 with a probability value (sig = 0.000), so the significant value is smaller than 0.05. This means the hypothesis which states that partially the tax knowledge variable has a significant influence on the compliance of land and building taxpayers in Cimanggung District. Then tax knowledge has an effect on taxpayer compliance by 44.3%, while 100%-44.3% = 56.7% is influenced by other factors that are not included in this research variable